A Comparative Study for Assess the Outcome of Alum and Herbal Mouthrinses on Plaque Control among 9–12-year-old Youth: A Randomized Research Trial - Prabhat Kumar Singh; Vikas Singh; Pradeep Tangade; Ankita Jain; Rangoli Srivastava; Yashi Sharma (Journal of Indian Association of Public Health Dentistry)
Background: Plaque on the teeth is encouraged to form by a variety of chemicals produced by the two types of bacteria that are present in dental biofilms. The main cause and driver of the development of oral diseases is plaque from the teeth. Aims and Objectives: To assess and compare the impacts of alum mouthwash, alkaline solution, and herbal mouthwash on plaque prevention in Youth. Materials and Methods: Ninety-nine healthy youngsters between the ages of 9 and 12 were recruited for the study and split into three groups with 33 participants each: Groups I, II, and III utilized mouthwash that contained alum (0.02 M), saline solution, and herbal mouthwash, respectively. For 30 days, every participant cleaned their mouth twice a day. Every participant’s plaque index score was recorded on the 1st, 15th, and 30th days of the trial. Results: Comparing the alum group (Group I) and the herbal group (Group III) to the saline group (Group II), there was a noticeable decrease in plaque at the 1st, 15th, and 30th days. Conclusions: The components in the herbal group (Group III) and alum group (Group I) showed efficacy in preventing the development of plaque, suggesting a potential use as a substitute for antibacterial mouthwash.